Improving the efficiency of hybrid combination preparation in rice breeding by a modified flowering stimulant - Zheng, Ling; Zhang, Shangxing; Xue, Fengying; Yun, Yifan; Liu, Pin; Yuan, Hua; Chen, Weilan; Qin, Peng; Wang, Yuping; Ma, Bingtian; Li, Shigui; Chen, Yong; et al. (International Journal of Agricultural and Biological Engineering, 2020)
The utilization of hybrid vigor is an important breakthrough in the history of rice breeding. To select the best hybrid combinations, breeders manually perform extensive testing of hybridizations between restorer and sterile lines, which is a laborious and time-consuming process. Here, we report that a modified flowering stimulant containing methyl jasmonate (MeJA), 6-benzylamine adenine and kinetin effectively promotes the flowering and seed set of male-sterile rice lines. Different concentrations of the ingredients were tested to identify an optimal formulation. Seed quality evaluation indicated that hybrid seeds from plants sprayed with the flowering stimulant had a higher germination rate than seeds from plants prepared by glume-cutting. In summary, the modified flowering stimulant described in this study may help reduce the labor requirement associated with hybrid rice breeding and improve yield and efficiency.Keywords: hybrid rice, cross, flowering stimulant, methyl jasmonate, kinetinDOI: 10.25165/j.ijabe.20201303.5632Citation: Zheng L, Zhang S X, Xue F Y, Yun Y F, Liu P, Yuan H, et al. Improving the efficiency of hybrid combination preparation in rice breeding by a modified flowering stimulant. Int J Agric & Biol Eng, 2020; 13(3): 36–40.